PENGARUH PROFITABILITAS DAN STRUKTUR KEPEMILIKAN YANG DIMEDIASI OLEH PENGUNGKAPAN CSR PADA PERUSAHAAN MANUFAKTUR - Sri Anawati (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This study aims to test the effect of Profitability and Ownership Structure on Corporate Value Mediated by Corporate Social Responsibility Disclosure.Sample used in this study is a company that is flat on the Indonesia Stock Exchange for the period 2019.The sample selection method uses purposive sampling so that sampling is in accordance with the researcher's criteria. The analytical tool used to test hypotheses is Partial Least Square. The results of this study found that Profitability, Institutional Ownership has a positive effect on the value of the company, Public influences the value of the company, Coorporate Social Responsibility has no positive effect on the value of the company, Profitability, Public Ownership has a positive effect on the disclosure of Corporate Social Responsibility. Profitability to the value of the company through mediation Corporate social responsibility does not have a positive and significant effect on the value of the company, Institutional ownership of the value of the company through mediation Corporate social responsibility has no positive and significant effect on the value of the company, Public ownership of the company's value through corporate mediating does not have a positive and significant effect on the value of the company.